COASTAL ZONE MANAGEMENT IN INDONESIA : ISSUE AND APPROCHES - Rokhmin Dahuri (JOURNAL OF COASTAL DEVELOPMENT, 1998)
The coastal zones and their embodied natural resources are a frontier area that offers Indonesian nation opportunities and challenges to enhance its economic development on a sustainable basis. Being the largest Archipelago State in the world, Indonesia is endowed with abundant and diverse coastal and marine resources. As natural resources on land are becoming scarce or difficult to develop, marine and coastal resources will be an importance resource for sustaining Indonesian economic development in the twenty first centuries. Furthermore, the shift of the global economic center from Atlantic to Pacific Rim will inevitably increase the use of Indonesia’s marine and coastal areas for various development activities, especially sea communication and transportation, fisheries and aquaculture, tourism, mining and energy, maritime industry, and coastal and offshore engineering. However, experience in developing marine and coastal resources during First Long-term Development Period (1969-1994) have resulted not only in economic successes but also caused environmental degradation at a level which threatens the sustainable capacity of marine and coastal ecosystems to support further Indonesia’s economic development. Case like water pollution in highly populated or industrializes areas, overfishing of some fish stock, physical destruction of important coastal ecosystems (especially mangrove and coral reef), and coastal resource use conflict among coastal users indicate such a threatened condition. In addition, the majority of coastal communities are still lingering on absolute poverty. The paper critically identifies and analyses the root of the problems, which threatens the sustainable capacity of coastal ecosystems, and suggests an alternative development paradigm provides a framework for reorientation of Indonesia’s development policies and programs with respect to coastal and marine resources to achieve sustainable development for the utmost benefits of all Indonesian people.